2019
DOI: 10.1097/md.0000000000018113
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is highly prevalent in malnourished inpatients and associated with higher mortality

Abstract: The impact of vitamin D deficiency on the recovery of patients with malnutrition remains undefined. Our aim was to study the prevalence of vitamin D deficiency in a well-characterized cohort of patients with malnutrition and its association with outcomes. Within this secondary analysis of a randomized controlled trial, we examined the association of vitamin D deficiency and adverse clinical outcomes over a follow-up of 180 days in hospitalized patients at risk for malnutrition. We measured 25-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…It has been estimated by the Swiss Federal Office of Public Health that large parts of the Swiss population have inadequate serum 25-hydroxy-vitamin D (25(OH)D) concentrations, particularly among the elderly, frail population. For example, a recent clinical multicentre study found that 60% of multimorbid medical inpatients had deficient vitamin D levels (<50 nmol/l) on admission and 25% were severely deficient (<25 nmol/l) [8]. In this study, vitamin D deficiency was associated with a 30% increase in mortality risk in a statistical regression model adjusted for demographics and comorbidities.…”
Section: Vitamin D Deficiencies In Switzerlandmentioning
confidence: 46%
“…It has been estimated by the Swiss Federal Office of Public Health that large parts of the Swiss population have inadequate serum 25-hydroxy-vitamin D (25(OH)D) concentrations, particularly among the elderly, frail population. For example, a recent clinical multicentre study found that 60% of multimorbid medical inpatients had deficient vitamin D levels (<50 nmol/l) on admission and 25% were severely deficient (<25 nmol/l) [8]. In this study, vitamin D deficiency was associated with a 30% increase in mortality risk in a statistical regression model adjusted for demographics and comorbidities.…”
Section: Vitamin D Deficiencies In Switzerlandmentioning
confidence: 46%
“…The trial protocol and the results of the main trial, as well as secondary outcomes, have been published previously. [4,11,[16][17][18][19][20][21][22] The Ethics Committee of Northwest and Central Switzerland (EKNZ) approved the study protocol in January 2014 (EKNZ; 2014_001).…”
Section: Methodsmentioning
confidence: 99%
“…Older adults 65þ deficient vitamin D levels at hospital admission, which was associated with higher mortality [111]. The prevalence of vitamin D insufficiency was highest in winter (JanuaryeMarch) with more than nine out of ten men being vitamin D deficient and/or insufficient [112].…”
Section: Nutrient Adultsmentioning
confidence: 99%